PENGARUH PEMBERIAN JUS NANAS TERHADAP PROSES PENYEMBUHAN LUKA PERINEUM PADA IBU NIFAS DI BPM Bd FITRIANI, SST TANJUNGPINANG - Arista, Ocfitri; Sulistyawati, Tri Ribut (Universitas Batam, 2020)
In Indonesia although a large number of women (96%) breastfeed their children in their lifetime, A study showed that 38% of mothers said that perineal pain increased on the seventh day after delivery, 60% of primiparous mothers had grade 2 perineal tears and 91% experienced grade 3 and grade 4 perineal tears. pineapple on the perineal wound healing process in postpartum mothers at BPM Fitriani, SST Tanjungpinang in 2020. This study used a pre-experimental research design carried out at BPM Fitriani, SST Tanjungpinang from February to July 2020. The population was all grade I post partum mothers. and second degree at BPM Bidan Fitriani, SST Tanjungpinang and a sample of 30 people with a purposive sampling technique. From the results of the study, before being given pineapple juice, respondents who experienced perineal wounds the average score was 5 out of a total score 6. Healing of perineal wounds after being given pineapple juice the average score was 4.5 out of a total score 6 There was an effect of pineapple juice on the wound healing process perineum in postpartum mothers where the value was significant p = 0.037 (<0.005). The conclusion is that there is an effect of pineapple juice on the perineal wound healing process in postpartum mothers at BPM Bidan Fitriani, SST. Suggestions for support from health workers, especially midwives, are expected to help mothers through the postpartum period, especially those with injuries to the perineum. giving pineapple juice can be an alternative to accelerate wound healing in the perineum.